2007
DOI: 10.1007/s00270-007-9026-5
|View full text |Cite
|
Sign up to set email alerts
|

Lymphangiography: Forgotten Tool or Rising Star in the Diagnosis and Therapy of Postoperative Lymphatic Vessel Leakage

Abstract: Since the advent of computed tomography, numbers and expertise in Lymphangiography (LAG) have markedly dropped. The intention of our study was to demonstrate the persisting diagnostic and therapeutic impact of LAG on the postoperative patient with known or suspected lymphatic vessel leakage. Between May 1, 1999, and April 30, 2006, we investigated pedal lipiodol-LAGs (18 monopedal, 2 bipedal) on 22 patients (16 male, 6 female) with known or suspected postoperative chylothorax, chylaskos, lymphocele, or lymphat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
94
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(97 citation statements)
references
References 25 publications
2
94
1
Order By: Relevance
“…In this study with overall 47 patients with chylous fistula, patients with contained chyle leaks represented the majority (n=34, 72.9%). These required total parenteral nutrition less frequently (44.1% vs. 92.3%), and had a shorter time to resolution (13 vs. 36 days) than those with diffuse chylous ascites (n=13)(15).The therapeutic use of bipedal lymphangiography with lipiodol has been described with occlusion rates from 35% to 70% (30,31,33) in patients with chylous ascites refractory to conservative treatment. A study by Alejandre-Lafont et al (n=43) demonstrated occlusion rates of 70% when the daily volume of chyle leakage was less than 500 ml (30).…”
mentioning
confidence: 94%
“…In this study with overall 47 patients with chylous fistula, patients with contained chyle leaks represented the majority (n=34, 72.9%). These required total parenteral nutrition less frequently (44.1% vs. 92.3%), and had a shorter time to resolution (13 vs. 36 days) than those with diffuse chylous ascites (n=13)(15).The therapeutic use of bipedal lymphangiography with lipiodol has been described with occlusion rates from 35% to 70% (30,31,33) in patients with chylous ascites refractory to conservative treatment. A study by Alejandre-Lafont et al (n=43) demonstrated occlusion rates of 70% when the daily volume of chyle leakage was less than 500 ml (30).…”
mentioning
confidence: 94%
“…Lymphography is helpful to visualize the anatomy of lymphatic vessels of the treatment-relevant region and the leakage site for preoperative planning of fistula occlusion [10,11]. Furthermore, lymphography itself is an effective, minimally invasive method not only for the detection but also for treatment of lymphatic leakage [10,12]. Recent studies show that magnetic resonance (MR) lymphography is a promising approach to identify specific features of lymphatic vessel leakage, but MR lymphography as a treatment option of lymphatic leakage cannot be possible [13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Kos et al [12], 22 patients underwent lymphography. 73.3% of the reported patients had an occlusion of the postoperatively damaged lymphatic vessel and did not undergo surgery after lymphography.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] In this report, we describe a case in which direct intranodal LAG was used as a definitive treatment for persistent chylous ascites after liver-kidney transplantation.…”
mentioning
confidence: 99%
“…3 This procedure has been described for diagnosing and treating chylous ascites after various thoracic and intra-abdominal procedures. Kos et al 1 reported 22 patients with lymph leaks who underwent Lipiodol LAG after surgical intervention. They reported the identification of the leak in 75% of the patients, and 55% demonstrated leak closure.…”
mentioning
confidence: 99%